Phased reconstruction of aorta after dissecting aortic aneurysm type I (by DeBakey) - I. I. Zhekov; V. I. Kravchenko; B. V. Cherpak; I. A. Osadovska; K. A. Khizhnyak; V. V. Vayda (Ukrainian Journal of Cardiovascular Surgery, 2017)
Aortic dissection – a tear in the aortic wall that causes blood to flow between the layers of the wall separating them from each other. Aortic dissection is an urgent condition that can quickly lead to death, even with optimal treatment. Mortality rate is up to 80%, and half of the patients die before admission. If the aortic diameter reaches 6 cm or more, the patient should be operated urgently. The goal of the surgery is to replace the ascending aorta and to prevent retrograde dissection and cardiac tamponade (the main cause of death).Objective. To present the clinical case of phased reconstruction of aorta after dissecting aortic aneurysm type I (by DeBakey).Materials and Methods. The article presents clinical case of a patient with dissecting aortic aneurysm of type I (by DeBakey) classification and its gradual reconstruction.Results and discussion. The goal of surgery is to replace the ascending aorta and to prevent retrograde dissection and cardiac tamponade (the main cause of death). Aortic valve reconstruction or it’s resuspension can be performed. When the structure of the aortic valve is impaired (Marfan syndrome, bicuspid aortic valve) it should be replaced.Conclusion. The choice of treatment depends on the type of dissection and its impact on other organs and body systems.1. Patients with ascending aorta dissection require urgent surgery and control of blood pressure.2. Patients with dissection in descending aorta are managed conservatively with tight control of blood pressure.3. Drug treatment followed by thoracic aorta endoprosthesis nowadays is used in the management of acute aortic aneurysms type B.